Teaching Electronic Literature in EFL Classrooms: The Know-What, The Know-How, and The Know-Why. - Rizal Octofianto Datau; Ari Setyorini (Tell : Teaching of English Language and Literature Journal, 2023)
Electronic literature has been broadly discussed for the last two decades along with the rapid development of new media. The ongoing debate has been concerned with its shifting form from printed text to digital text which brings along several changes in the way literature must be seen. However, studies on this subject are still limited to its L1 setting and most of the discussions focus on its cultural material discourses. To fill in the gap, this paper discusses the necessity of bringing up the practical application of electronic literature in EFL classrooms. The discourse revolves around addressing several key inquiries: the types of electronic literature viable as learning materials in ELT (the know-what), the teaching strategies through which electronic literature can be effectively taught in ELT (the know-how), and the fundamental rationale underscoring the importance of teaching electronic literature to EFL students (the know-why).